Primary pleural intermediate hemangioendothelioma with pleural effusion as the only manifestation - Jiang, Juan; Li, Yuanyuan; Hu, Chengping; Zhou, Jianhua; Yang, Huaping; Cao, Liming; Deng, Pengbo (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
Intermediate hemangioendothelioma is a group of rare tumors of vascular origin that show a borderline biological behavior and commonly arise in extremities, trunk, head or neck. Intermediate hemangioendothelioma originating in pleura is extremely rare. Herein we describe a case of primary pleural intermediate hemangioendothelioma in a 48-year-old man presenting with pleural effusion only. The patient was diagnosed by pleura biopsy and immunohistochemistry in our hospital. Even though neither systemic chemotherapy nor surgery was applied, he got relieved gradually and sustained asymptomatic during follow-up for 10 months.